Karakteristik Bolu Kukus dengan Penambahan Ekstrak dan Kelopak Bunga Telang - Nawasari Indah Putri Sejati; Rifai Agung Mulyono (Jurnal Akademika Baiturrahim Jambi, 2022)
Telang flower is a plant that has a health effect on the body. 10% telang flower can be used as a natural food coloring. Steamed cake is also a traditional food favored by community. Steamed cake usually uses synthetic food coloring to attract the consumers. This study aimed to examine the antioxidant capacity, chemical characteristics, and organoleptic properties of steamed cake with the addition of extract and petals of telang flower. This research using experimental approach conducted in April–December 2020. The product analyzed for antioxidant capacity using total phenol and DPPH methods, chemical characteristics with proximate analysis, and organoleptic properties using hedonic and rankings hedonic. Data were analyzed using ANOVA with Duncan Multiple Range Test. The results were the extract and petals of telang flower significantly affected the total phenol content and antioxidant activity of steamed cake with relatively fluctuating values. In addition, the addition of telang flower extract and petals in steamed cake increased the water content but decreased the fat content significantly, decreased the protein and ash content not significantly. While the value of fiber and carbohydrates are relatively fluctuating. Telang flower extract and petals also had no effect on sensory attributes such as color, taste, aroma, and texture of steamed cake. The products are liked by panelist. It was concluded that telang flower can be used as food coloring for steamed cake without changing the product’s organoleptic properties.